Substantivando: An Educational Game for Teaching Nouns in Elementary School - Costa, Desirée Xavier da; Pereira, Williane Gabriele S.; Lima, Pedro Dimas da C.; Santos, Suellen Trindade dos; Estevam, Leonardo da C.; Pontes, Paulo André I.; Fernandes, José Guilherme dos S.; Seruffo, Marcos Cesar da R. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2024.241022, 2024)
Teaching nouns in Elementary School presents various challenges, and gamification emerges as a promising strategy to overcome them, promoting playful and effective learning. This work presents the gamified educational game Substantivando, which combines quizzes, scoring systems, and immediate feedback to enhance students' learning. The game was validated with 26 students through a questionnaire adapted to evaluate the quality of the educational game, focusing on the dimensions of motivation, user experience, and learning effectiveness. The results indicate that Substantivando not only supports the teaching of nouns, but also enriches the educational process by providing a stimulating, fun, and enriching learning experience.